2012
DOI: 10.1186/1750-1172-7-36
|View full text |Cite
|
Sign up to set email alerts
|

Miglustat therapy in the French cohort of paediatric patients with Niemann-Pick disease type C

Abstract: BackgroundNiemann-Pick disease type C (NP-C) is a rare neurovisceral lysosomal lipid storage disease characterized by progressive neurological deterioration. Published data on the use of miglustat in paediatric patients in clinical practice settings are limited. We report findings from a prospective open-label study in the French paediatric NP-C cohort.MethodsData on all paediatric NP-C patients treated with miglustat in France between October 2006 and December 2010 were compiled. All patients had a confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
86
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 34 publications
14
86
0
5
Order By: Relevance
“…A systematic review on later findings of clinical trials [21] revealed that miglustat can slow down the progression of neurologic symptoms in all NPC patients, yet the therapeutic benefit is greater in those with a late diagnosis compared with early childhood onset. Although miglustat provided the proof-of-principle for the efficacy of substrate reduction strategies, miglustat still has its limitations, which are mostly related to unwanted side effects including visceromegaly, hematologic abnormalities, diarrhea, intestinal carbohydrate malabsorption and weight loss [6,10,30,31,32,33]. However, our treated mice did not show any obvious gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…A systematic review on later findings of clinical trials [21] revealed that miglustat can slow down the progression of neurologic symptoms in all NPC patients, yet the therapeutic benefit is greater in those with a late diagnosis compared with early childhood onset. Although miglustat provided the proof-of-principle for the efficacy of substrate reduction strategies, miglustat still has its limitations, which are mostly related to unwanted side effects including visceromegaly, hematologic abnormalities, diarrhea, intestinal carbohydrate malabsorption and weight loss [6,10,30,31,32,33]. However, our treated mice did not show any obvious gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…Miglustat was approved in Europe in 2009, and has since been approved in a number of other countries. As a result, clinical experience with this drug is increasing [7,8,16,21]. …”
Section: Introductionmentioning
confidence: 99%
“…While neurological deterioration was seen to commence in one patient at the time his seizures became refractory to antiepileptic medication, pre-existing epilepsy (before miglustat therapy) or the onset of epilepsy during miglustat therapy did not appear to affect neurological outcomes in cases where seizure control was maintained using antiepileptic medications [11]. In our patient, the antiepileptic therapy using valproate and lamotrigine showed no efficacy for more than 1 year; however, our patient’s condition dramatically improved after miglustat therapy was started and he became seizure free 4 months after its introduction.…”
Section: Discussionmentioning
confidence: 99%